Hubungan Peran Bidan, Dukungan Keluarga, dan Kecemasan dengan Perilaku Kunjungan ANC Ibu Hamil TM III - Noorianti, Rika; Sugesti, Retno; Lisca, Shinta Mona (Q PRESS, 2023)
Antenatal care is the second pillar in Safe Motherhood which is a means for mothers to be better prepared for childbirth. This research uses descriptive analytic with cross sectional approach. The population of this study was 40 pregnant women and the sampling technique used was total sampling with a sample of 40 pregnant women. The results of this study indicate that there is a significant relationship between the role of midwives and the behavior of ANC visits for pregnant women TM III in the context of preparation for childbirth, obtained a P value of 0.001, there is also a significant relationship between family support and visitation behavior. ANC of TM III pregnant women in preparation for labor obtained a P Value of 0.004, but there was no significant relationship between anxiety and behavior of ANC visits of TM III pregnant women in preparation for childbirth and obtained a P Value of 0.116. Suggestions from this study are that midwives and families can provide as much support and information as possible about pregnancy and childbirth so that pregnant women's confidence and awareness of the importance of ANC visits in preparation for childbirth can be awakened.